IN–VITRO PHARMACEUTICAL EVALUATION OF TWO BRANDS OF DISPERSIBLE ACETYL SALICYLIC ACID TABLETS AVAILABLE IN OMAN - Khan, Shah Alam; Al Shabibi, Maryam Nasser; Nazmi, Abdul Salam (Faculty of Pharmacy Universitas Gadjah Mada, Yogyakarta, Skip Utara, 55281, Indonesia, 2013)
Acetyl salicylic acid (ASA), a non-steroidal anti-inflammatory drug (NSAID) is widely used for its analgesic, antipyretic, antiinflammatory and anti-thrombotic action. The aim of the present study was to investigate the pharmaceutical equivalence of two brands of dispersible ASA tablets marketed in Oman. Two different brands of dispersible ASA tablets (300mg) were purchased from the retail pharmacy outlets and their pharmaceutical quality were assessed by using in-vitro tests as per the British Pharmacopoeia (BP) and unofficial standards as recommended by the manufacturers. The assessment of tablets included the evaluation of uniformity of weight and diameter, friability, crushing strength, disintegration and chemical assay by volumetric titration and colorimetric methods to determine the content of active pharmaceutical ingredient (API). Both brands of the ASA tablets passed the BP standards for uniformity of weight and diameter, disintegration, friability and crushing strength. However one of the two brands did not comply with the standard assay of content of active ingredient. Thus based on these results it can be concluded that these two brands of ASA are not pharmaceutically equivalent.Key words: ASA tablets, pharmaceutical equivalence, disintegration, volumetric method.